Editorial - Dybowska, Ewa; Ruszkiewicz, Dominika (Multidisciplinary Journal of School Education, 2024)
The main topic of this issue of the Multidisciplinary Journal of School Education is support in educational settings, including spiritual support. The articles presented here take a broad view of education, inviting us to ponder the spiritual, religious, and axiological aspects of educational reality. By bringing together educational theory, philosophy, and practice, they offer diverse perspectives on the issue of support as well as multiple methodological approaches. Consequently, the image of the individual—whether student, teacher, or parent—that emerges from these studies results from complex interaction processes, which involve individuals’ relationships with others and the outside world, as well as their inner selves. Viewed from various anthropological angles, individuals are seen in the context of everyday situations and social connections. Above all, they are recognized as spiritual beings in search of transcendent values, meaning, and moral focus, particularly in the educational context. The articles in this issue encourage consideration of various theoretical approaches to teaching and invite critical reflection on concepts such as support, spirituality, and meaningful engagement in education.